Penguatan Kompetensi Resusitasi Neonatus pada Perawat melalui Pelatihan Berbasis Pedoman American Heart Association (AHA) - Indah Purnama Sari; Wulan Pramadhani; Oki Isnanto (CV. ALIM'SPUBLISHING, 2026)
Neonatal asphyxia remains one of the leading causes of neonatal mortality in Indonesia, and timely, competent resuscitation by nurses is critical to improving newborn survival. This community service activity aimed to strengthen nurses' neonatal resuscitation competency through an intensive training program based on the 2025 American Heart Association (AHA) and American Academy of Pediatrics Guidelines for Cardiopulmonary Resuscitation and Emergency Cardiovascular Care. The training was conducted for 25 nurses working in the perinatology, delivery room, and neonatal intensive care unit of Awal Bros Batam Hospital using a one-group pretest-posttest design, combining lectures, algorithm-based discussion, and high-fidelity manikin simulation covering the Newborn Chain of Care, initial steps of resuscitation, positive-pressure ventilation, chest compression, and updated umbilical cord management recommendations. Results showed a significant increase in nurses' knowledge and skill scores after training, along with improved self-confidence in managing simulated neonatal emergencies. This activity demonstrates that structured, guideline-based simulation training is an effective and feasible strategy to enhance nurses' readiness in delivering safe, standardized neonatal resuscitation, supporting broader efforts to reduce neonatal mortality.